Pariwisata Berkelanjutan Danau Sarantangan, Singkawang, Kalimantan Barat - Stephanie Rosanto; Khania Carennia (PolimdoSains, 2022)
Sarantangan Lake is located in Sagatani Village, South Singkawang Subdistrict, 22 km from Singkawang City. This lake is a natural tourism potential with an area of ​​400 hectares. With the Covid-19 pandemic, the world of global tourism has experienced a tremendous shock. Sarantangan lake is one of the tourist destinations that has felt the impact of the reduced level of tourist visits, both local and foreign. To anticipate this, the sustainable tourism development strategy that is formulated must be able to take into account the existing situations and conditions during and after the pandemic. The research method used in this research is descriptive qualitative method. Lake Sarantangan has excellent natural and cultural potential but needs to be developed more professionally and regularly. The role of the government, local communities, and tourists to work hand in hand in optimizing the existing potential is very much needed. The potential that is owned must be able to be promoted on a large scale with the help of funds from the central government, especially with the status of Sarantangan Lake as a tourist destination which is part of the Super Priority Destinations. The quality of human resources and existing facilities must also be continuously improved to provide economic and social benefits for the surrounding community. It also cannot be forgotten, that various efforts and strategies must be carried out to maintain the authenticity and preservation of nature and local culture.